2020
DOI: 10.1111/acer.14419
|View full text |Cite
|
Sign up to set email alerts
|

High Alcohol–Preferring Mice Show Reaction to Loss of Ethanol Reward Following Repeated Binge Drinking

Abstract: Background Beyond yielding high blood ethanol (EtOH) concentrations (BECs), binge‐drinking models allow examination of drinking patterns which may be associated with EtOH’s rewarding effects, including front‐loading and consummatory successive negative contrast (cSNC), a decrease in intake when only water is available to subjects expecting EtOH. The goals of the current study were to broaden our understanding of these reward‐related behaviors during binge EtOH access in high alcohol–preferring (HAP) replicate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 41 publications
0
29
0
Order By: Relevance
“…Nevertheless, it can be challenging to test the effect of alcohol drinking on the nervous system in rodents because adult female rodents tend to drink significantly more g/kg alcohol than their male counterparts [ 42 , 59 63 , 84 , 85 ]. Studies that show no sex differences in alcohol consumption can also be found, which may reflect differences in species, strain, age, drinking paradigm, and study design [ 46 , 47 , 63 , 65 , 86 – 88 ]. While it is well known in the field that adult female rats drink more alcohol than males, the specific differences in patterns of drinking between males and females and their effects on the brain are not well understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, it can be challenging to test the effect of alcohol drinking on the nervous system in rodents because adult female rodents tend to drink significantly more g/kg alcohol than their male counterparts [ 42 , 59 63 , 84 , 85 ]. Studies that show no sex differences in alcohol consumption can also be found, which may reflect differences in species, strain, age, drinking paradigm, and study design [ 46 , 47 , 63 , 65 , 86 – 88 ]. While it is well known in the field that adult female rats drink more alcohol than males, the specific differences in patterns of drinking between males and females and their effects on the brain are not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…For example, others have described “front-loading” as a burst of rapid drinking behavior at the start of the session when rodents first have access to alcohol [ 35 48 ]. Front-loading is found to be specific to rewarding substances, as mice that previously exhibited front-loading behavior to alcohol did not show this same behavioral response for water [ 45 47 ]. Other rewarding substances are capable of inducing front-loading in mice and rats, including sweet high-fat liquids and sodium solution to sodium-depleted rats, which makes front-loading behavior a consistent behavioral phenotype for seeking and consuming rewards [ 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…In experiment 2, we assessed whether repeated QuA exposures alters the pattern of compulsive‐like QuA drinking after 3 weeks of daily DID, because we utilized a within‐subjects design in experiment 1 which resulted in 2 QuA exposures. Since alcohol front‐loading is thought to represent motivation to drink alcohol because the consumption occurs prior to the absorptive effects of alcohol (Ardinger et al, 2020; Linsenbardt and Boehm, 2014, 2015; Wilcox et al, 2014), we also sought to determine the pattern of front‐loading in QuA‐drinking mice. Finally, we determined BACs following QuA drinking.…”
Section: References Quinine Concentration (μM) Alcohol History and Consumption Model Use Of Alcohol Naïve Control Sexes Usedmentioning
confidence: 99%
“…Additionally, front-loading can be suppressed with conditioned taste aversion with a bitter solution (LiCl) in the first 9 minutes of access (Baird et al, 2005). Reward expectation can induce front-loading to non-rewarding solutions in alcohol-exposed mice that receive water when alcohol is expected (Ardinger et al, 2020). Increasing the effort to obtain alcohol with an FR3 schedule suppressed the total alcohol intake in both males and females; however subtle sex differences in front-loading remained, as females showed front-loading while it was notably reduced in males.…”
Section: Front-loading Drives Sex Differences In Alcohol Intakementioning
confidence: 99%
“…Operant self-administration in rodents is useful for modeling voluntary alcohol consumption in humans, while maintaining a level of experimental control needed for precise tracking and manipulation of alcohol drinking behavior (Brown et al, 1998;Elmer et al, 1987aElmer et al, , 1987bGeorge, 1987;Samson, 1986, 1985;June and Gilpin, 2010;Risinger et al, 1998); reviewed in (Green and Grahame, 2008;Jeanblanc et al, 2019). We used this approach to map out the dynamic microstructural patterns in drinking in male and female adult rats to explore various aspects of drinking behavior such as rapid drinking at the start of a session i.e., "front-loading" (Ardinger et al, 2020;Baird et al, 2005;D'Aquila et al, 2012;Davis, 1996;Lardeux et al, 2013;Linsenbardt and Boehm, 2015;Robinson and McCool, 2015). We also manipulated operant parameters of alcohol availability to further probe these sex differences in drinking patterns.…”
Section: Introductionmentioning
confidence: 99%